2020
DOI: 10.21307/ane-2019-031
|View full text |Cite
|
Sign up to set email alerts
|

Updating the picture of layer 2/3 VIP-expressing interneuron function in the mouse cerebral cortex

Abstract: For years, interneurons expressing vasoactive intestinal peptide (VIP) interneurons and their function within the neocortex have been shrouded in mystery. Their relatively small size and minimal representation in the cortex have made investigation difficult. Due to their service role performed in co-operation with glia and blood vessels to supply energy during neuronal activation in the brain, the contribution of VIP interneurons to local neuronal circuit function was not appreciated. VIP interneurons in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…This confirms that GFP expression had not ‘leaked’ into other inhibitory classes, which is in agreement with previous studies 37 , 48 . The relatively large proportion of co-labeling with anti-CR antibodies agrees with the finding that many VIP neurons in the upper layers of cortex are CR-expressing bipolar cells 52 , 55 , 57 , 58 . The small proportions that were co-labeled with anti-CCK and anti-NPY antibodies is also congruent with previous findings 55 57 .…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This confirms that GFP expression had not ‘leaked’ into other inhibitory classes, which is in agreement with previous studies 37 , 48 . The relatively large proportion of co-labeling with anti-CR antibodies agrees with the finding that many VIP neurons in the upper layers of cortex are CR-expressing bipolar cells 52 , 55 , 57 , 58 . The small proportions that were co-labeled with anti-CCK and anti-NPY antibodies is also congruent with previous findings 55 57 .…”
Section: Resultssupporting
confidence: 85%
“…Using 2-photon laser scanning microscope (2PLSM) in vivo we demonstrate that a subset of multipolar VIP neurons, located in superficial cortical layers, have high spine densities on their dendrites that ramify in cortical L1. Their morphological and electrophysiological characteristics are similar to the bursting type of small VIP cells 22 , 44 , 49 – 52 . Long-term imaging, over days to weeks, revealed that their spines have strikingly different dynamics as compared to spines of pyramidal neurons, displaying a higher instantaneous probability of disappearing.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…VIP + interneuron-selective interneurons show a variety of unique spiking behaviors during sustained depolarization including ''irregular'' behavior with single APs firing randomly; ''bursting'' behavior with three-five high-frequency APs discharged initially, followed by single APs at random intervals''; and ''stuttering'' behavior with clusters of spikes separated by silent periods of varying duration (Posluszny, 2019). VIP + interneurons preferentially target SST + interneurons and a fraction of PV + interneurons (Turi et al, 2019).…”
Section: Interneuron-selective/disinhibitory Interneuronsmentioning
confidence: 99%
“…Neurons expressing the vasoactive intestinal polypeptide (VIP) compose about 40% of the 5‐HT3aR group of cortical interneurons (Tremblay et al., 2016), and they have some intriguing features. Unlike the PV and SST interneurons, many of the VIP interneurons, whose soma is located mostly in layer 2/3 (L2/3), exhibit a bipolar dendritic morphology (Bayraktar et al., 2000; Connor & Peters, 1984; Posłuszny, 2019; Prönneke et al., 2015). Functionally, the VIP interneurons play a major role in the modulation of cortical function, especially through disinhibition of pyramidal neurons (Ayzenshtat et al., 2016; Fu et al., 2014; Karnani et al., 2016; Lee et al., 2013; Pfeffer et al., 2013; Pi et al., 2013; Walker et al., 2016).…”
Section: Introductionmentioning
confidence: 99%